ROMA. Una geografia della numerazione civica. - Valerio Zunino (GEOmedia, 2019)
The new geographical toponymy of Rome, performed by STUDIO SIT srl, totally comes from a field survey started in late 2017. Single house numbers compete with each other as for their accuracy and updating. Points are close to 500.000, reaching the total of those for Milan, Turin, Naples and Genoa. Sometimes the enormous surface of the municipality of Rome has represented a trouble for collectors, also with damaged roads, environmental findings and later built. But now, completeness and accuracy of this data put it strongly to the attention of most influential location intelligence players.